2022
DOI: 10.1017/jsl.2022.27
|View full text |Cite
|
Sign up to set email alerts
|

On the Uncountability Of

Abstract: Cantor’s first set theory paper (1874) establishes the uncountability of ${\mathbb R}$ . We study this most basic mathematical fact formulated in the language of higher-order arithmetic. In particular, we investigate the logical and computational properties of ${\mathsf {NIN}}$ (resp. ${\mathsf {NBI}}$ ), i.e., the third-order statement there is no injection resp. bijection from  $[0,1]$ to ${\mathbb N}$ . Working in Kohlenbach’s higher-order Reverse Mathematics, we show that ${\mathsf {NIN}}$ and ${\ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…In this light, implicit in much of mathematical practise is the following most basic principle about countable sets: a set that can be mapped to N via an injection (or bijection) can be enumerated. This principle was studied in [73,86,88] as part of the study of the uncountability of R. In this paper, we continue the study of this principle in Reverse Mathematics (RM hereafter) and connect it to well-known 'household name' theorems due to Bolzano-Weierstrass, Cantor, Jordan, and Heine-Borel, as discussed in detail in Section 1.2. We assume basic familiarity with RM, also sketched in Section 1.3.1.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In this light, implicit in much of mathematical practise is the following most basic principle about countable sets: a set that can be mapped to N via an injection (or bijection) can be enumerated. This principle was studied in [73,86,88] as part of the study of the uncountability of R. In this paper, we continue the study of this principle in Reverse Mathematics (RM hereafter) and connect it to well-known 'household name' theorems due to Bolzano-Weierstrass, Cantor, Jordan, and Heine-Borel, as discussed in detail in Section 1.2. We assume basic familiarity with RM, also sketched in Section 1.3.1.…”
mentioning
confidence: 87%
“…Since Cantor space with the lexicographic ordering and [0, 1] with its usual ordering are intimately connected, we take the former ordering to be fundamental. We have shown in [73] that BWC fun 0 is 'explosive' in that it yields the much stronger Π 1 2 -CA 0 when combined with the Suslin functional, i.e. higher-order Π 1 1 -CA 0 .…”
mentioning
confidence: 93%
“…Finally, the uncountability of R can be studied in numerous guises in higher-order RM. For instance, the following are from [57,58], where it is also shown that many extremely basic theorems imply these principles, while Z ω 2 cannot prove them. • For a countable set A ⊂ [0, 1], there is y ∈ [0, 1] \ A.…”
Section: Definition 19 [Enumerable Sets Of Reals]mentioning
confidence: 99%
“…• NBI: there is no bijection from [0, 1] to N In particular, as shown in [58][59][60], the principles NBI and NIN are hard to prove in terms of conventional 2 comprehension, while the objects claimed to exist are hard to compute in terms of the other data, in the sense of Kleene's computability theory based on S1-S9 ( [38,47]). As shown in [67], this hardness remains if we restrict the mappings in NIN and NBI to well-known function classes, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation